KONSEP PENDIDIKAN BERKELUARGA DALAM KITAB ‘UQUDULLIJAIN RELEVANSINYA DENGAN PENDIDIKAN ISLAM DI INDONESIA - Muqo robin (Prodi PGMI IAIN Salatiga, 2009)
This study is an attempt to know (1) biography of the author of the book 'Uqudullijain. (2) the attitude of Nawawi in the book 'Uqudullijain. (3) Relevancy of the concept of family in the book 'Uqudullijain with Islamic education in Indonesia. This study use induction and deductive method to analyze the data. The research findings indicate that family education in the book